2020
DOI: 10.1016/j.geoderma.2019.114090
|View full text |Cite
|
Sign up to set email alerts
|

Durable and ductile double-network material for dust control

Abstract: Dust generation is a worldwide issue due to its serious deleterious effects on the environment, human health and safety, and the economy. Although various dust suppression methods have been used for decades, some critical drawbacks in state-of-the-art technology still remain unsolved, such as short-lasting, ground water impact, and prone to water. This work reports a soil stabilizer based on non-toxic material and forms a ductile and durable double-network in soil, namely "D 3 soil stabilizer", which not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The destruction and degradation of topsoil is a key factor in reducing soil fertility. [1][2][3] Among various methods of soil stabilization, polymer-based approaches have been suggested, 4 which allow the mechanical characteristics of the soil to be enhanced, [5][6][7][8][9][10] suppressing dust transfer [10][11][12][13] and decreasing soil washout. [14][15][16] To date polyacrylamide (PAM) is regarded as the world's anti-erosion standard; this term is applied to various copolymers composed of acrylamide and acrylic acid salt.…”
Section: Introductionmentioning
confidence: 99%
“…The destruction and degradation of topsoil is a key factor in reducing soil fertility. [1][2][3] Among various methods of soil stabilization, polymer-based approaches have been suggested, 4 which allow the mechanical characteristics of the soil to be enhanced, [5][6][7][8][9][10] suppressing dust transfer [10][11][12][13] and decreasing soil washout. [14][15][16] To date polyacrylamide (PAM) is regarded as the world's anti-erosion standard; this term is applied to various copolymers composed of acrylamide and acrylic acid salt.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of polymeric stabilizers is mainly determined by the characteristics of soil substrates and polymer binders 7–10 . As to the latters, amphiphilic stabilizers of dual nature with an affinity both to the hydrophilic and hydrophobic surfaces show a pronounced advantage over other polymers 11–14 …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the improvement of soil strength, the precipitated CaCO 3 in EICP can fill the voids within the soil matrix thereby reducing porosity and permeability [18,[116][117][118][119][120][121][122][123][124][125][126][127][128]. Knorr [116] applied the EICP technique to control the impacts of water and wind erosion using different soil types such as Ottawa F60 sand, silty-sand and mine tailings.…”
Section: Erosion and Dust Controlmentioning
confidence: 99%
“…They found that EICP-treated samples exhibited a threefold improvement in terms of the mass of soil lost compared to untreated specimens. Many other researchers have evaluated the effectiveness of the EICP technique for dust control [118][119][120][121] and surface water erosion mitigation [122][123][124][125], and have found the results to be satisfactory.…”
Section: Erosion and Dust Controlmentioning
confidence: 99%